Government Support and Policy Design to Improve MSME’s Performance - Dendy Ramadhona; Wirman Syafri; Dedeh Maryani; Mansyur Achmad (International Journal Labs, 2023)
This study aims to analyze the effect of financial support and non-financial support from the Government of Pesawaran Regency on the performance of MSMEs in Pesawaran Regency. Furthermore, this study also analyzes the proposed policy model for the Pesawaran Regency Government to improve the performance of MSMEs. This study uses mixed methods, namely a combination of quantitative and qualitative analysis. Data in the quantitative analysis in this study came from primary data obtained through the distribution of questionnaires given to MSMEs in Pesawaran Regency, Lampung Province. The results of the questionnaire will be analyzed using the Structural Equation Model method using AMOS software. While qualitative data were obtained from interviews with informants which were then analyzed using the coding method with the N-Vivo software. The results of the analysis show that financial and non-financial support have an effect on the performance of MSMEs in Pesawaran Regency, Lampung. The most influential financial support is related to giving awards and appreciation to MSMEs that excel. The most influential non-financial support is related to digital technology coaching and training in business and entrepreneurship. This study proposes 2 policy models, the first model includes MSME training, capital assistance and incentives for MSME achievements, collaboration and building and developing marketing centers for MSME products in pesawaran. The second model namely INDIRA covers MSME Integration, Digitalization and MSME Regeneration.